Independent risk factors for ICU mortality after left ventricular assist device implantation. Issue 2 (2nd September 2019) - Piffard, Marianne; Nubret‐Le Coniat, Karine; Simon, Olivier; Leuillet, Sébastien; Rémy, Alain; Barandon, Laurent; Ouattara, Alexandre
Abstract: Left ventricular assist devices (LVADs) are used as an alternative therapy for heart transplantation in patients with advanced heart failure. However, the mortality rate of these patients remains relatively high. A large proportion of deaths after LVAD implantation occur during intensive care unit (ICU) stay. We conducted a retrospective study to identify the risk factors for all‐cause ICU mortality in patients with an implanted LVAD. Between January 1, 2008 and December 31, 2016, 70 consecutive patients who had received an LVAD were analyzed. The median ICU length of stay was 14 days (IQR: 8‐31) and 16 patients (22.9% [95%CI: 13.1‐32.7]) died in the ICU. The 90‐day mortality rate was 25.7% (95%CI: 15.5‐35.9). The main causes of ICU mortality were: multiple organ failure, stroke, and hemorrhagic events. The univariate analysis identified the following perioperative risk factors for all‐cause ICU mortality: hypertension, preoperative platelet count, preoperative white cell count, inotropic support before LVAD implantation, mechanical ventilation before LVAD implantation, renal replacement therapy before LVAD implantation, short‐term mechanical support before LVAD implantation, INTERMACS class 1 to 2, low intraoperative platelet count, low early postoperative hemoglobin level, low early postoperative platelet count, low early postoperative pH, and massive perioperative blood transfusion. In the multivariate logistic regression analysis, only mechanical ventilation before LVAD implantation was retained as an independent risk factor for ICU mortality (OR = 11.96 [95%CI: 2.67‐53.45], P  < .01). These findings confirm that most deaths after LVAD implantation occur in the ICU. Patients that receive mechanical ventilation preoperatively have the highest risk of death. This confirms the need to actively treat respiratory failure and to wean patients from respiratory support before LVAD implantation. Such a strategy offers the best opportunity to initiate active rehabilitation.